Children literature in Nigeria: the Yoruba example (2008)
"The aesthetic and therapeutic effects of literature on the life effect both the old and young. Yoruba oral literature accords due respect to children in its poetry and drama as it has a myriad of renditions like songs, lullabies, poems and folktales for their listening and participation enjoyment. In contemporary Nigeria love for written children literature in Yoruba is dying as many authors do not write for children while publishers also show little interest in publishing materials in the indigenous languages. This paper examined the prospect of children written literature in Yoruba by considering the efforts of writers so far and the problems facing it today. Suggestions on how to sustain it and improve on its teaching in schools in the 21st century are also offered. "